Sex of the Fetus can be Associated with Placental Pathologies in Premature Deliveries - Munim, Wasan; Kamel , Niran; Raheem Kareem, Alaa; Rasool Hussein Aal-Saleh, Mustafa; Luay Subhi, Mohammed; Abdulkareem Ali Al-Dujaili, Sarah (Diyala Journal of Medicine, 2020)
Background: There are many pregnancy complications that are significantly associated with the gender of the fetus; one of them is preterm labour, which is an important obstetric problem that may lead to many perinatal morbidity and mortality. Objective: To find out whether there is a relation between the findings of placental pathology of premature deliveries and gender difference. Patients and Methods: Fifty deliveries before a 32 week gestational age. Obstetrical, and placental histological findings have been compared among all males (n=25), and females (n=25) premature neonates. Results: The male premature fetus had distribution rate in maternal age, gestation age at the time of delivery, placental weight, and feto-placental weight-ratio in females, but a higher birth-weight centile ([55.09±11.3] versus [43.09±8.2]). Histopathology of the placenta found no significant association of fetal-sex with acute inflammatory lesions (p=0.09), intra-placental vascular pathological findings, or utero-placental vascular pathology. However, the chronic inflammatory lesion showed a higher pathological score in male fetuses than in the females (p=0.01). Conclusion: Premature deliveries with less than thirty-two weeks, the male fetal-sex had higher placental pathological lesions, suggesting maternal immunological responses towards the invading trophoblasts. The immunological background of these pathological lesions needs further studies.